2009
DOI: 10.1111/j.1440-1827.2009.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple IgG4‐related sclerosing lesions in the maxillary sinus, parotid gland and nasal septum

Abstract: IgG4-related sclerosing disease is recognized as a distinct clinicopathological entity. It is well known that this disease can occur in the salivary, lacrimal and pituitary glands, in the head and neck region. The nasal cavity is an extremely rare site of involvement of IgG4-related sclerosing disease. Herein is reported a case of multiple IgG4-related sclerosing lesions in the maxillary sinus, parotid gland and nasal septum. A 73-year-old Japanese man presented with nasal obstruction and tumors of the right m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 28 publications
(50 reference statements)
2
68
1
1
Order By: Relevance
“…Upper respiratory tract presentation of the disease is rare (Table I) [3,8,9,11,12,13,14,15,16]. A review of the available literature showed only single cases of IgG4-RD of the oral cavity with presentation in the palate, tongue, floor of the mouth, and upper and lower gingiva [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Upper respiratory tract presentation of the disease is rare (Table I) [3,8,9,11,12,13,14,15,16]. A review of the available literature showed only single cases of IgG4-RD of the oral cavity with presentation in the palate, tongue, floor of the mouth, and upper and lower gingiva [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Recent reports have shown destructive IgG4 lesions involving the maxillary sinus 12 and nasal septum, 13 both of which resolved after treatment with systemic corticosteroids. Gill et al reported salivary duct carcinoma arising in IgG4-related fibrosclerosis involving the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In the head and neck region, IgG4RSD commonly manifests as chronic sclerosing sialadenitis, chronic sclerosing dacryoadenitis, and lymphoplasmacytic hypophysitis. 1,10,11 IgG4RSD is considered to result from an imbalance in the regulatory immune reaction, 12 but the mechanisms are still unclear. IgG4RSD develops predominantly in males 13 and involves Ն2 sites in most patients, though some patients may have disease involving only 1 organ.…”
Section: Discussionmentioning
confidence: 99%
“…There is insufficient radiologic data for IgG4RSD affecting the nasal cavity and paranasal sinuses. [1][2][3] We present a case of IgG4RSD mimicking an invasive malignant tumor in the nasal cavity and maxillary sinuses on both sides.…”
mentioning
confidence: 99%
See 1 more Smart Citation